2018
DOI: 10.1177/1523422318756636
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of the Employee Work Passion Appraisal Model Using Self-Determination Theory

Abstract: The Problem. Employee work passion theory offers an appraisal-based approach that explains how work passion is formulated in individuals. Self-determination theory postulates that the satisfaction of three basic psychological human needs (competence, relatedness, and autonomy) is essential for individuals to flourish and thrive at work. The role of basic psychological need satisfaction in the employee work passion appraisal process is yet to be examined. The Solution. We investigated the relations between empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 76 publications
4
23
0
1
Order By: Relevance
“…One reason for this is the job satisfaction of social workers, which is recognized in many studies and could act as a compensating factor for the previous subscales. For example, the professional practice of social work is oriented toward promoting personal or collective well-being, which impacts job satisfaction [ 45 , 46 , 47 ]. In the current health crisis, job satisfaction may have emerged as a counterbalance to the high values of the previous subscales, especially EE.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for this is the job satisfaction of social workers, which is recognized in many studies and could act as a compensating factor for the previous subscales. For example, the professional practice of social work is oriented toward promoting personal or collective well-being, which impacts job satisfaction [ 45 , 46 , 47 ]. In the current health crisis, job satisfaction may have emerged as a counterbalance to the high values of the previous subscales, especially EE.…”
Section: Discussionmentioning
confidence: 99%
“…Team-level shared leadership fosters feelings of being competent, autonomous, and empowered, thus enabling employees to improve their performance. In addition, positive appraisals of work environment characteristics lead to positive work intentions to use discretionary effort and improve performance (Thibault-Landry et al, 2018). Studies have found that these intentions deriving from psychological processes are reliable predictors of both in-role and extra-role behaviors (Dubinsky & Skinner, 2002).…”
Section: Passion At Work At Individual Level and Individual Outcomesmentioning
confidence: 99%
“…In addition, positive appraisals of work environment characteristics, namely, shared feelings of passion at work, result in positive work intentions to use discretionary effort and improve performance (Thibault-Landry et al, 2018). Studies have found that these intentions derived from psychological processes are reliable predictors of both in-role and extra-role behaviors (Dubinsky & Skinner, 2002).…”
Section: Theoretical Contributionmentioning
confidence: 99%
“…Si bien los resultados obtenidos particularmente en torno a la pasión obsesiva podrían resultan sorprendentes, dada la connotación negativa del constructo (Autor & Autor, en prensa), son plenamente consistentes con la teoría y la evidencia disponible. En efecto, diversos estudios (Carpentier, Mageau, & Vallerand, 2012;Curran, Hill, Appleton, Vallerand, & Standage, 2015;Lavigne, Forest, & Crevier-Braud, 2011;Thibault-Landry, Egan, Crevier-Braud, Manganelli, & Forest, 2018;Zito & Colombo, 2017) señalan que los individuos apasionados se encuentran completamente abocados a su trabajo. Los altos montos de esfuerzo y dedicación invertidos en la ejecución de sus tareas explicarían la mayor absorción y motivación intrínseca, así como la posibilidad de disfrute y satisfacción mientras estén involucrados en su trabajo; aún, entre los obsesivamente apasionados.…”
Section: Discussionunclassified